In Vivo and In Vitro Analyses of Titanium-Hydroxyapatite Functionally Graded Material for Dental Implants. - Wang, Xinhua; Wan, Chengpeng; Feng, Xiaoxia; Zhao, Fuyan; Wang, Huiming (BioMed Research International, 2021)
Purpose. The stress shielding effect caused due to the mechanical mismatch between the solid titanium and the surrounding bone tissue warrants the utilization of a mechanically and biologically compatible material such as the titanium-hydroxyapatite (Ti-HA) functionally graded material (FGM) for dental implants. This study is aimed at fabricating a Ti-HA FGM with superior mechanical and biological properties for dental implantation. Materials and Methods. We fabricated a Ti-HA FGM with different Ti volume fractions (VFs) using HA and Ti powders. Ti-HA was characterized by studying its mechanical properties. Cytotoxicity was examined using a Cell Counting Kit-8 assay and an LDH cell cytotoxicity assay. Scanning electron microscopy was performed on an XL30 environmental scanning electron microscope (ESEM). Alkaline phosphatase (ALP) and transforming growth factor (TGF-β1) expressions were quantitatively monitored using enzyme-linked immunosorbent assay (ELISA) kits. The expressions of TGF-β receptors and ALP genes were measured using real-time polymerase chain reaction. The Ti-HA FGM dental implants were placed in beagle dogs. Microcomputed tomography (CT) and hard tissue slices were performed to evaluate the bone-implant contact (BIC) and bone volume over total volume (BV/TV). Results. The density and mechanical properties of the Ti-HA exhibited various graded distributions corresponding to VF. Based on the results of the Cell Counting Kit-8 (CCK-8) and lactate dehydrogenase (LDH) assays, the difference in cytotoxicity between the two groups was statistically nonsignificant (P = 0.11). The ALP and TGF-β1 levels were slightly upregulated. The transcript levels of ALP and TGF-βRI were higher in the Ti-HA groups than in the Ti group at 7 days, whereas the transcript levels of TGF-βRII exhibited no obvious increase. The BIC did not exhibit significant differences between the Ti and Ti-HA FGM groups (P = 0.0504). BV/TV showed the Ti-HA FGM group had better osteogenesis (P = 0.04). Conclusion. Ti-HA FGM contributes to the osteogenesis of dental implants in vivo and in vitro.